2004
DOI: 10.1111/j.1467-7652.2004.00090.x
|View full text |Cite
|
Sign up to set email alerts
|

Over‐expression of a transcription factor regulating ABA‐responsive gene expression confers multiple stress tolerance

Abstract: SummaryUnfavourable environmental conditions, such as drought, freezing and high salinity, are major limiting factors of plant productivity. Plants perceive and respond adaptively to such 'abiotic stress' conditions, and the adaptive process is controlled mainly by the phytohormone, abscisic acid (ABA). The hormone, whose level increases under various stress conditions, functions as a signal to trigger adaptive responses that include changes in gene expression patterns. We have recently reported transcription … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
54
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(58 citation statements)
references
References 58 publications
(80 reference statements)
2
54
0
2
Order By: Relevance
“…At the molecular level, certain heat-shock proteins are commonly elicited in response to various stress conditions (Vierling 1991;Feder 1999;Sørensen et al 2003). Likewise, in the Arabidopsis model system, shared elements among drought, salinity, and temperature extreme response pathways have been identified, such as the DREB transcription factors and the phytohormone abscisic acid (ABA) (Liu et al 1998;Kim et al 2004;Mauch-Mani and Mauch 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…At the molecular level, certain heat-shock proteins are commonly elicited in response to various stress conditions (Vierling 1991;Feder 1999;Sørensen et al 2003). Likewise, in the Arabidopsis model system, shared elements among drought, salinity, and temperature extreme response pathways have been identified, such as the DREB transcription factors and the phytohormone abscisic acid (ABA) (Liu et al 1998;Kim et al 2004;Mauch-Mani and Mauch 2005).…”
mentioning
confidence: 99%
“…In the model system Arabidopsis thaliana, the physiological basis of these resistance mechanisms has been pursued with the ultimate goal of elucidating the biochemical pathways involved in stress perception, signal transduction, and adaptive response (e.g., Seki et al 2001Seki et al , 2002Kreps et al 2002;Hazen et al 2003;Takahashi et al 2004;Liu et al 2005). While many stress responses appear to be specific to different forms of stress, it is clear that some stress responses are general and potentially confer tolerance to multiple types of stress (Chinnusamy et al 2004;Kim et al 2004). The genes associated with these general stress responses may yield insight into biochemical networks underlying stress resistance and may provide targets for stress-resistance engineering in plant species.…”
mentioning
confidence: 99%
“…(Robertson et al, 1994), and ABA pretreatment can increase cell viability and growth upon HS (Zhang and Fevereiro, 2007). In addition, the overexpression of transcription factor ABF3 in ABA signaling induced high-temperature tolerance in transgenic Arabidopsis (Kim et al, 2004). These results suggested that ABA could also be involved in the response to heat stress.…”
Section: Introductionmentioning
confidence: 59%
“…These results indicate that the functions of AtNRP1 in thermal adaptation may be independent of the HSF-controlled regulon. Ding et al, 2008), and some studies have indicated that the ABA content was increased in response to heat stress (Kim et al, 2004;Zhang and Fevereiro, 2007). So we propose AtNRP1 may function in thermotolerance through the ABA signaling pathway.…”
Section: Atnrp1-mediated Thermosensitivity Is Independent Of Hs-relatmentioning
confidence: 99%
“…These genes contain cis-regulatory elements in their promoter regions, such as the abscisic acid-responsive element (ABRE), which is regulated by various upstream transcription factors, or TFs (Tuteja 2007). Among those TFs, a small family of ABRE-binding proteins has been identified, i.e., ABRE-binding factors (ABFs) or ABAresponsive element-binding proteins (AREBs) (Kim et al 2004). Expression of these proteins is also induced by ABA (Choi et al 2000).…”
Section: Introductionmentioning
confidence: 99%